The Formation Mechanism of Impulse Buying in Short Video Scenario: Perspectives From Presence and Customer Inspiration - Gao, Peng; Zeng, Yuanyuan; Cheng, Yu (Frontiers in Psychology, 2022)
It has been found in many cases that consumers are prone to exhibit impulsive buying behavior that is manifested as being immediate, emotional and irresponsible especially under short video scenario. Supported by the customer inspiration theory, this article explores the psychological mechanism underlying impulse purchase in short videos that differentiates the traditional web shopping by the strong sense of presence in short video marketing. On the basis of a questionnaire survey and three laboratory experiments, this study examines the relationship among presence, customer inspiration, and impulse purchase intention. The empirical results point to the fact that social presence, co-presence and physical presence have significant positive effects on impulse purchase intention, and that customer inspiration mediates the effect of social presence, physical presence and co-presence on impulse purchase intention. Furthermore, it is indicated that social and co-presence have stronger influences on impulse purchase intention than physical presence, thus proving a stronger effect of social factors on impulse purchase intention than physical factors in short video environment. The research results testify the impact of presence on consumer behavior in the upgrading short video marketing and provide valuable reference for marketing strategies to shorten consumers’ decision-making time in short video purchase.